No pain no gain: Feelings and performance in sport - Moen, F.; Firing, K.; Vittersø, J. (Journal of Athletic Enhancement, 2016)
This study aimed to explore how the emotion of joy could play a central role during different sport activities among young elite athletes. The participants in this study were 211 junior athletes in sports who were undergoing their High School education at different schools specializing in elite sports. Our results showed that eudaimonic emotions were associated with episodes that are considered to be demanding for an athlete, such as core activities, whereas hedonic emotions were associated with easier situations such as routine activities. Moreover, eudaimonic emotions were for the most part associated with the ability to realize athletes' potential. Finally, playful activities reported the highest score on both hedonic and eudaimonic emotions.